A history of Serbian mediaeval law - Šarkić, Srdjan (Medieval law and its practice, 2023)
This book explores the complete history of Serbian law in the Middle Ages, covering the 12th to the 15th centuries, which until now has been largely unstudied in international scholarship. Firmly rooted in primary source research and showing strong awareness of the contemporary historical context, this comprehensive study examines different types of law ? such as criminal law, constitutional law, and civil law ? and the various legal systems and procedures in place during this time, offering a valuable synthesis while also presenting new views and novel interpretations of Serbian legal history